2013
DOI: 10.1038/eye.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Partial posterior hyaloidectomy for macular disorders

Abstract: Purpose To evaluate the effect of partial posterior hyaloidectomy (PPH) in preventing iatrogenic retinal breaks related to the induction of a posterior vitreous detachment (IPVD) Methods Fifty-nine patients who necessitated IPVD for an epiretinal membrane or macular hole were included in this prospective, interventional case series. Extensive removal of vitreous gel, close to the retina, was conducted before IPVD under 23 G (gauge)-vitrectomy system. The PPH involved the limited extent of IPVD and limited remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Kim et al suggested that partial posterior hyaloidectomy, as they had termed it, could minimize the traction on the vitreous base and therefore reduce the risk of iatrogenic retinal breaks. 121 They reported a reduction in retinal break formation from 21% to 5% compared with conventional 23 G surgery, although they did note two postoperative retinal detachments in the modified technique group. Cullinane and Cleary also suggested a similar technique, but primarily to reduce the incidence of symptomatic field defects after surgery.…”
Section: Other Advances In Surgical Techniques and Equipmentmentioning
confidence: 93%
“…Kim et al suggested that partial posterior hyaloidectomy, as they had termed it, could minimize the traction on the vitreous base and therefore reduce the risk of iatrogenic retinal breaks. 121 They reported a reduction in retinal break formation from 21% to 5% compared with conventional 23 G surgery, although they did note two postoperative retinal detachments in the modified technique group. Cullinane and Cleary also suggested a similar technique, but primarily to reduce the incidence of symptomatic field defects after surgery.…”
Section: Other Advances In Surgical Techniques and Equipmentmentioning
confidence: 93%
“…28,40,41 Furthermore, a partial posterior hyaloidectomy, where the hyaloid membrane is intentionally detached during vitrectomy, is performed routinely as part of macular hole surgery in patients with diabetic or idiopathic retinopathy in order to limit traction and improve visual outcomes. 42,43 In summary, pre-retinal delivery of rAAV appears to be well tolerated in the 13-LGS and, even at a considerably lower dose volume, results in increased retinal transduction compared to the deep vitreous intravitreal delivery route. If developed further, the pre-retinal injection route could represent a novel method by which to administer gene therapy for the treatment of inherited retinal disease, particularly in younger patients with intact posterior hyaloid membranes and solid un-liquified vitreous.…”
Section: Discussionmentioning
confidence: 95%
“…They reported successful results from 3 patients, without any significant complications. In another study, Kim et al [ 8 ] performed posterior hyaloid separation slightly beyond the temporal vascular arcade in 59 eyes with macular disorders and compared it with 57 eyes that underwent complete vitrectomy. The incidence of iatrogenic peripheral retinal breaks was significantly lower in eyes with the partial vitrectomy (3.4%), compared to complete vitrectomy (16%).…”
Section: Discussionmentioning
confidence: 99%